The Family Is The Basic Structure Of Society, The Source Of Moral Education In Society - Safiya NIYOZOVA; Muqima AMANULLAEVA; Dildora NIYOZOVA (Euro Asian Journal Publishing, 2025)
In this article role family in society, relationships moral educational family, laws Constitution Republic Uzbekistan and relationships family case discussion decision they take
Keywords: family; concept family; upbringing family